Strategi Pembelajaran Guru Sekolah Minggu dalam Menghadapi Anak yang Pasif - Boni Boni; Yonatan Alex Arifianto; Reni Triposa (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2024)
Sunday school teachers must be an example for every child. Sunday school teachers must also be able to provide exciting teachings and involve children in learning so that passive children can participate in learning. Using descriptive qualitative methods, this research can be concluded that. Teachers in Sunday schools can create effective teaching methods that involve children in teaching, such as the question-and-answer method, to encourage children to be active in the learning process, enabling them to be enthusiastic in the teaching process. Sunday school is essential in teaching, helping, and encouraging children to understand what the Bible provides as the right way to live in Christ. Children can shape their attitudes, behavior, and character by following God's commands through the Word of God, taught by parents and Sunday schoolteachers in the Christian faith.